Implications of failure to achieve a result from prenatal maternal serum cell‐free DNA testing: a historical cohort study. (6th December 2017) - Chan, N; Smet, M‐E; Sandow, R; da Silva Costa, F; McLennan, A
Abstract : Objective: To investigate the pregnancy outcomes in a cohort of women who failed to obtain a result in non‐invasive prenatal testing (NIPT). Design: Historical cohort study. Setting: A multicentre private practice in Sydney, Australia. Population: Women who failed to obtain a result from NIPT ( n = 131). Methods: The maternal characteristics, antenatal investigations and pregnancy outcomes for these women were compared with those who obtained a result at the same practice and to the general Australian obstetric population. Main outcome measures: Antenatal investigations: pregnancy‐associated plasma protein‐A (PAPP‐A), free β ‐human chorionic gonadotrophin ( β ‐hCG), placental growth factor (PlGF), uterine artery pulsatility index (PI), mean arterial pressure (MAP). Pregnancy outcomes: chromosomal abnormality, pre‐eclampsia, gestational diabetes, small‐for‐gestational‐age (SGA), preterm delivery. Results: Only 1.1% of NIPT samples failed to return a result. This cohort was significantly older and had significantly increased weight compared with the general Australian obstetric population. Pregnancy outcomes were available for 94% of the cohort. There were significantly higher rates of chromosomal aneuploidies (6.5% versus 0.2%, P < 0.0001), pre‐eclampsia (11% versus 1.5%, P < 0.0001) and gestational diabetes (23% versus 7.5%, P < 0.0001) compared with the general obstetric population. Rates of preterm delivery and SGA were elevated but did not reach significance. Antenatal investigations demonstrated decreased PAPP‐A MoM (0.75 versus 1.14, P < 0.0001), decreased free β ‐hCG (0.71 versus 1.01, P < 0.0001) and increased uterine artery PI (1.79 versus 1.65, P = 0.02). Conclusion: Women who fail to obtain a result from NIPT are at increased risk of adverse pregnancy outcomes, in particular chromosomal aneuploidy, gestational diabetes and pre‐eclampsia. Funding: None received. Tweetable abstract: Women who fail to obtain a result from cell‐free DNA NIPT are at increased risk of adverse pregnancy outcomes. Tweetable abstract: Women who fail to obtain a result from cell‐free DNA NIPT are at increased risk of adverse pregnancy outcomes.